2021
DOI: 10.3390/ijerph18157875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Midwife-Coordinated Maternity Care Intervention (ChroPreg) vs. Standard Care in Pregnant Women with Chronic Medical Conditions: Results from a Randomized Controlled Trial

Abstract: The proportion of childbearing women with pre-existing chronic medical conditions (CMC) is rising. In a randomized controlled trial, we aimed to evaluate the effects of a midwife-coordinated maternity care intervention (ChroPreg) in pregnant women with CMC. The intervention consisted of three main components: (1) Midwife-coordinated and individualized care, (2) Additional ante-and postpartum consultations, and (3) Specialized known midwives. The primary outcome was the total length of hospital stay (LOS). Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…O primeiro fator é referente ao aumento no número de processos agendados, como cesarianas eletivas, versões cefálicas externas e induções ao parto; isso é consistente com a atual pesquisa baseada em evidências. (21,(23)(24)(25) E o segundo fator depende do tipo de paciente atendida, como a etnia subamericana, as nulíparas e as mulheres que apresentam comorbidades médico-obstétricas. Esse aumento da carga de trabalho observado é consistente com os achados de outros estudos, (1,2,8,21,23) pois atualmente enfrentamos um aumento na atenção aos processos crônicos, gerados pelo aumento da gemelaridade, pelo aumento da idade materna, pelos nascimentos prematuros, bem como pelo aumento das técnicas de reprodução assistida.…”
Section: Resultsunclassified
“…O primeiro fator é referente ao aumento no número de processos agendados, como cesarianas eletivas, versões cefálicas externas e induções ao parto; isso é consistente com a atual pesquisa baseada em evidências. (21,(23)(24)(25) E o segundo fator depende do tipo de paciente atendida, como a etnia subamericana, as nulíparas e as mulheres que apresentam comorbidades médico-obstétricas. Esse aumento da carga de trabalho observado é consistente com os achados de outros estudos, (1,2,8,21,23) pois atualmente enfrentamos um aumento na atenção aos processos crônicos, gerados pelo aumento da gemelaridade, pelo aumento da idade materna, pelos nascimentos prematuros, bem como pelo aumento das técnicas de reprodução assistida.…”
Section: Resultsunclassified
“…Current studies are now focusing on the evaluation of clinical- and cost-effectiveness in midwifery care models for women experiencing complex pregnancy and women with chronic medical conditions [ 20 – 22 ]. In a randomized controlled trial comparing midwife-coordinated maternity care intervention with standard care for women with chronic medical conditions, de Wolff et al found an increased level of satisfaction with maternity care among women who received midwife coordinated maternity care intervention [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals should receive training in respectful and evidence-based childbirth care, and policy frameworks must safeguard women's rights during pregnancy and childbirth. By taking proactive steps to prevent obstetric violence, we can ensure that all women receive the respectful and safe care they deserve during this signi cant life event (32,(37)(38)(39)(40).…”
Section: What Does This Study Adds To the Clinical Workmentioning
confidence: 99%
“…Healthcare professionals should receive training in respectful and evidence-based childbirth care, and policy frameworks must safeguard women's rights during pregnancy and childbirth. By taking proactive steps to prevent obstetric violence, we can ensure that all women receive the respectful and safe care they deserve during this signi cant life event (32,(37)(38)(39)(40).Despite numerous studies worldwide aiming to identify obstetric violence, research in Turkey remains limited.Furthermore, no studies have examined this issue before women are discharged from the hospital. This study aims to explore women's experiences of obstetric violence and the factors in uencing these experiences during childbirth.The research questions are as follows:1.…”
mentioning
confidence: 99%